Religious and Cultural Moderation in Responding to the Challenges of Globalisation in Local Communities - Baktiar Leu (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study explores the implementation of religious moderation in the cultural system of Kupang City society, East Nusa Tenggara, which has diverse demographic characteristics. Using a critical ethnographic approach with data collection techniques of participatory observation, in-depth interviews, and document analysis, this study identifies four main manifestations of religious moderation: (1) shared rituals and traditions, (2) local wisdom in conflict resolution, (3) interfaith social networks, and (4) transformation of religious values ??in contemporary cultural practices. Rituals such as Bonet Manekat and Haroan Bupolo function as interfaith meeting spaces, while local wisdom mechanisms such as Suf Natoni and Lais Manekat effectively manage potential religious-based conflicts. Interfaith social networks formed through the customary kinship system (bela-metan) become a moral infrastructure that forms the ethics of interfaith relations. However, the study also identifies challenges in the form of the influence of globalization, the politicization of religious identity, economic transformation, and the weakening of the transmission of local wisdom values. In response, the community developed a strategy for revitalizing tradition, strengthening interfaith dialogue based on culture, transforming moderation values ??through contemporary arts and culture, and integrating religious moderation values ??into regional development policies. These findings enrich the understanding of the dialectical relationship between religion and culture and provide a new perspective in the implementation of religious moderation policies that are contextual and based on local wisdom